Application of DNA molecules in nature- inspired technologies: a mini review - Semchenko, Igor V.; Khakhomov, Sergei A. (Frontiers in Nanotechnology, 2023)
The DNA molecule is considered as an object of nature-like technologies, with the focus on the special electromagnetic properties of DNA-like helices. This is the difference from the traditional approach to the DNA molecule as the repository of genetic information. DNA-like helices are regarded as artificial micro-resonators, or “meta-atoms,” exhibiting both dielectric and magnetic properties, that are equally pronounced. The article presents methods for creating spatial structures directly from DNA molecules, as well as from DNA-like helices. It is shown that the design of metamaterials and metasurfaces should be carried out considering the special electromagnetic properties of DNA-like helices. This will make it possible to obtain the required properties of metamaterials and metasurfaces and achieve advantages over other types of artificial structures.